KAJIAN MASYARAKAT PULUTAN SEBAGAI PERAJIN KERAMIK UNTUK MENINGKATKAN EKONOMI KELUARGA (Studi Kasus Ibu Rumah Tangga Sebagai Perajin Keramik Tradisional Di Desa Pulutan Kecamatan Remboken) - Laloan, Jovelien J N (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2017)
This study is comprised of housewives who are in the Village Pulutan in SubDistrict Remboken who jumped on the small industries or home industries that are working in addition to their regular job as a housewife, which are taking care their husband and children, cooking, washing clothes etc. as the core power in the house. Based on the obtained data show that the highest incomes above , then the above three million of 11 respondents or 61,1 percent, then the above Rp 2 million of 5 responder or 27,7percent , then at over 1,000 .000 a respondent stayed 2 or 11,1 per cent. Looking at the distribution of income is the highest number of respondents 11 or 61,1 percent are on incomes above Rp 3,000,000, while the distribution of income while the lowest in over one million is a number 2 or 11,1 percent of the respondents is the lowest income of the respondent. It turned out that the above data show that with no additional work for housewives there was an increase in revenue. Conclusions through the research found that respondents family income has increased because most income is through the work of the husbands of various professions coupled with the work of housewives. As a suggestion to the community artisans to maintain quality and enhance the creative and innovate to be ready to compete to further develop the marketing area for both national and international level.Government be expected to pay attention to the industry in order to the needs of craftsmen, especially the need of capital for developing businesses and increasing skills through training in accordance with technological advances. Keywords: Community Craft, Ceramics.